Novel amphiphilic cyclodextrins: synthesis, characterization and properties - Rachel Auzély-Velty; Jean-Pierre Dalbiez; Stéphane Moutard; Bruno Perly; Florence Djedaïni-Pilard (ՀՀ ԳԱԱ հրատ.)
A new class of amphiphilic cyclodextrins have been obtained by grafting one single cholesterol moiety on the primary face of cyclodextrins.
Keywords: Biology; Biochemistry